Supply Chain Management in the Age of Digitalization: Revealing the Trends of SCM 4.0 - Pirvulescu, Petronela; Enevoldsen, Peter (ExcelingTech, 2019)
Digitalization is becoming one of the most debated technological trends radically changing how enterprises run and affect entire value chains across organizations. Factors such as globalization, increased data flow, complexity in supply chain operations, and more demanding and critical customer requirements are changing the nature of modern supply chains. The current research reveals how digitalization is reshaping supply chains and how different regions and industries are adapting to digitalization by investigating: the emerging digitalization trends in supply chain strategies, the global geographical impact of digitalization trends, and the impact on different types of business industries. The research is based on a comprehensive statistical analysis conducted on 119 scientific and management consulting studies. The study reveals that digitalization is becoming a revolutionary trend with an increasing pattern of interest from governments, organizations, and academic researchers in the form of nine main digitalization trends applied in various business industries and regions.